Recognizing and Overcoming Burnout in Breast Imaging. Issue 1 (25th February 2019) - Mainiero, Martha B; Parikh, Jay R
Abstract: Burnout is a psychological syndrome created by chronic job stress, and it is typified by emotional exhaustion, depersonalization, and feelings of decreased personal accomplishment. In physicians, burnout occurs at alarming rates, and it is on the rise. High burnout rates are ubiquitous in radiology across multiple subspecialties. We know of no study specifically examining burnout among breast imaging radiologists, but given the rates across multiple specialties in radiology, we must assume that a significant portion of breast imaging radiologists also experience burnout. As breast imaging increases in volume and complexity, we must find new ways of practicing that help achieve a healthy work environment.